Conical-beam antenna with four notch slots - Ren, Hengjiang (2013)
Conical-beam antennas are widely used in satellite communication and radar systems. In this paper, a 4-element array consisting of four notch slots is proposed to generate conical-beam radiation. Simulated results are presented to demonstrate the good performance of its conical-beam radiation when the array elements are fed in phase with equal amplitude.